Fish polyculture as affected by culture season, stocking density and breed, under subtropical conditions of Egypt - MARAI, I F M; GABR, H A; AKAR, A M (The Indian Journal of Animal Sciences, 2014)
Effects of culture season, stocking density and breed, under Egyptian sub-tropical conditions, were studied on fish polyculture. The body weight, growth rate and fish yield were higher (P